The Impact of Parenting, Online Game Usage, and Peer Interaction to Elementary School Students' Academic Achievement - Jefryadi, Jefryadi; Setiawati, Lilis; Fatmita AS, Lusi; Devi, Devi (Bulletin of Counseling and Psychotherapy, 2024)
This research explores the impact of parenting, online game usage, and peer interaction on elementary school (SD) student’s academic achievement. Various factors often affect academic achievement, including environment, family, digital habits, and social relationships. With the development of technology and the changing dynamics of family, it is vital to understand how these factors mutually interact and affect the student’s academic development. Type research descriptive associative explaining​ the extent of the impact of parenting, online game usage, and peer interaction on elementary school student’s academic achievement in Lubuk Linggau. This research uses a sample of 150 respondents from 3000 elementary school students in Lubuk Linggau. Path analysis uses the SPSS program to process data. The research results show that parenting, online game usage, and peer interaction significantly affect elementary school students' academic achievement. However,​ there are research findings that parents do not affect academic achievement, as mediated by peer interactions. These results show that parents must implement pattern-supportive care​ for student development​, limit excessive online game usage, and monitor interaction with their students' social lives to ensure positive academic achievement